PENGEMBANGAN MEDIA BERBASIS SMARTPHONE MENGGUNAKAN SMART APPS CREATOR UNTUK MENDUKUNG PEMBELAJARAN DARING PADA MATERI FLUIDA STATIS DI SMA NEGERI 1 TELAGA - Julkifli Adam; Raghel Yunginger; Ritin Uloli; Dewi Diana Paramata; Tirtawaty Abdjul; Nova Elysia Ntobuo (Jurnal Pendidikan Fisika Undiksha, 2023)
This research is research and development by adapting the 4-D Thiagarajan, Semmel and Semmel (Define, Design, Development, Disseminate) development model to produce smartphone-based media products using Smart Apps Creator that are feasible in terms of validity, practicality and effectiveness. media for learning to support static fluid daring material at Telaga 1 State High School, Gorontalo Regency. The research sample is 19 students of class XI Science Department. The results showed that smartphone-based media products met the eligibility criteria for learning media. In terms of validity, it meets the criteria of Very Valid with an average score of 3.87 for material experts and 3.82 for media design experts. In terms of practicality, it meets the criteria of Very Good with a percentage of 99% for learning implementation and Good selection with a percentage of 82.45% for student responses. In terms of effectiveness, it meets the Very Good criteria with a percentage of 94.67% for student activities and presentations of 95% of students fulfill the KKM. Keywords: Learning Media, Smartphones, Smart Apps Creator, Online Learning